Titanium-rare earth compound catalyst and method for alcoholysis of polyethylene glycol terephthalate
By using titanium-rare earth compound catalyst in the chemical regeneration process of polyethylene terephthalate, the depolymerization reaction is promoted, and the problems of low depolymerization rate and high catalyst residue in the prior art are solved, and the problem of low depolymerization rate and high catalyst residue in the prior art is achieved. The efficient and low-cost PET regeneration process obtains high-purity BHET products, supporting the closed-loop recycling of PET.
Patent Information
- Application Number
- CN202310841232.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-07-10
AI Technical Summary
In the prior art, the depolymerization rate of polyethylene terephthalate (PET) is low, the catalyst usage is large, and the catalyst residue in the target product is high, resulting in poor quality of regenerated products and the amount of ethylene glycol usage is Increase material and recycling costs greatly.
Using titanium-rare earth compound catalysts, including titanium-containing compounds and rare earth catalysts, the carbonyl oxygen coordination of polyethylene terephthalate through the inner hollow orbit of the rare earth catalyst is promoted to promote the depolymerization reaction and improve the depolymerization. and yield, and reduce the catalyst residue by optimizing process conditions such as reaction temperature, pressure and time.
The PET depolymerization rate is >99.5%, the polymerization degree of the depolymerization product is low, the content of BHET monomer is >95wt%, the process is simple and the energy consumption is low, and the product purity is >97.0%, which significantly improves the yield and purity of BHET and reduces the catalyst residue. The quantity of waste PET is efficiently recycled and reused.
Smart Images

Figure BDA0004331645340000072 
Figure BDA0004331645340000101 
Figure BDA0004331645340000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical degradation of waste polyester and relates to a titanium-rare earth composite catalyst and a method for alcoholyzing polyethylene terephthalate. Background Art
[0002] Polyethylene terephthalate (PET, referred to as polyester) is a thermoplastic resin with excellent performance. It is widely used in textile fibers, food packaging and other fields. Its usage is huge, but the amount of recycling and reuse is very small. Most of the PET waste will be landfilled or incinerated after use, causing great damage to the ecological environment. Therefore, the effective use of waste resources and the recycling and reuse of waste polyester products are urgent issues that need to be solved in the polyester field.
[0003] The recycling methods of waste polyester are mainly divided into physical recycling and chemical recycling. Physical recycling refers to the recycling of waste polyester products after impurities, cleaning, crushing and drying, and then melt granulation and re-molding. In the presence of impurities and pollutants, melt granulation will reduce the molecular weight of the recycled PET material. Therefore, additional antioxidants, chain extenders, processing aids, etc. need to be added during the recycling process. The product performance is degraded in each cycle, the number of recycling times is limited, and the product performance is poor.
[0004] Chemically recycled polyester is to depolymerize waste polyester into monomers or polymerization intermediates, separate and purify them, obtain high-purity monomers, and then polymerize them into high-quality recycled polyester, truly realizing the closed-loop recycling from "polymer-monomer-polymer" to obtain high-value multi-variety recycled products. Compared with other chemical recycled polyester methods, alcoholysis technology is relatively mature, and ethylene glycol alcoholysis can be directly scaled up using existing industrial PET polymerization equipment due to mild reaction conditions and high safety factor, which is easy to achieve industrialization and continuity, and has high economic benefits. However, due to the limitation of equilibrium reaction, it is difficult to achieve a high depolymerization rate in ethylene glycol alcoholysis, and there will be a large number of oligomer products in the depolymerization product, which makes the separation and purification process difficult. In order to improve the depolymerization rate and increase the yield of the target product, on the one hand, a higher content of catalyst is added, and on the other hand, the ethylene glycol / PET ratio is increased. However, if the content of the depolymerization catalyst is too high, it will lead to high catalyst residues in the target product, which will cause serious thermal degradation side reactions of the recycled product and affect the quality of the recycled polyester; on the other hand, increasing the amount of ethylene glycol feed will not only greatly increase the material cost, but also greatly increase its recovery cost.
[0005] In the existing chemical method of regenerating polyester, the use of titanium catalysts has higher selectivity and catalytic activity, and has no obvious harm to the environment and human body. It is a highly efficient green environmentally friendly catalyst. However, it still has the disadvantages of high catalyst addition amount, high catalyst residue in the target product, serious side reactions of the regenerated product, poor color, and difficulty in obtaining high-quality regenerated products; in addition, the amount of ethylene glycol used is large, and the material cost and ethylene glycol recovery cost will increase accordingly.
[0006] Therefore, it is necessary to provide a more suitable alcoholysis catalyst for chemically regenerated polyester. Summary of the invention
[0007] The invention aims to solve the problems in the prior art that when polyethylene terephthalate (PET) is regenerated, the chemical depolymerization rate is low, the polymerization degree in the depolymerization product is high, the amount of catalyst used is large, and the depolymerization product bis(2-hydroxyethyl) terephthalate (BHET) has low yield and purity, high oligomer content, and is difficult to recycle. A titanium-rare earth composite catalyst that can be used for PET alcoholysis and a method for alcoholyzing PET using the catalyst are provided.
[0008] In order to achieve the above-mentioned object, the first aspect of the present invention provides a titanium-rare earth composite catalyst, wherein the titanium-rare earth composite catalyst comprises: a titanium-containing compound and a rare earth catalyst;
[0009] Wherein, the titanium-containing compound is selected from at least one of alkyl titanate, diol titanium, titanium phosphate, and organic-inorganic hybrid titanium;
[0010] Wherein, the rare earth catalyst is selected from acetylacetone rare earth catalyst.
[0011] In the present invention, when the titanium-rare earth composite catalyst is used for depolymerization of materials containing polyethylene terephthalate, the rare earth catalyst contained therein is used as a depolymerization co-catalyst. The inner empty orbital of the rare earth element in the rare earth catalyst can coordinate with the lone pair of electrons of the carbonyl oxygen on the polyethylene terephthalate to carry out a catalytic reaction, thereby increasing the positive charge of the carbonyl carbon, which is beneficial to the nucleophilic attack of the hydroxyl group on the added diol on the carbonyl carbon atom on the polyethylene terephthalate when depolymerizing the materials containing polyethylene terephthalate, thereby accelerating the depolymerization reaction and improving the yield of the depolymerization product.
[0012] A second aspect of the present invention provides a method for alcoholysis of polyethylene terephthalate, the method comprising:
[0013] (1) in the presence of a protective gas and a catalyst, subjecting an alcohol and a material containing polyethylene terephthalate to a depolymerization reaction to obtain a depolymerization liquid;
[0014] (2) purifying the depolymerization liquid to obtain a product containing bis(2-hydroxyethyl) terephthalate;
[0015] Wherein, the catalyst is the titanium-rare earth composite catalyst described in the first aspect of the present invention.
[0016] Through the above technical solution, the present invention can achieve the following beneficial effects:
[0017] (1) The titanium-rare earth composite catalyst for alcoholysis of PET developed by the present invention has the advantages of high efficiency, high selectivity, low addition amount, and PET depolymerization rate of >99.5%. After the depolymerization is completed, the degree of polymerization of the depolymerization product is only 1-3, and the total content of BHET monomer, BHET dimer, and BHET trimer in the depolymerization product is >99wt%, of which the BHET monomer content is >95wt%.
[0018] (2) The titanium-rare earth composite catalyst developed by the present invention has no risk of catalyst residue and can significantly improve the BHET yield compared with the use of pure titanium catalyst to depolymerize PET.
[0019] (3) The titanium-rare earth composite catalyst alcoholysis PET process developed by the present invention is simple in process and low in energy consumption, and can directly obtain a BHET product with HPLC purity>97.0%.
[0020] (4) The BHET obtained by the method of the present invention can be directly used to prepare PET polyester products or other high value-added products, thereby realizing the closed-loop recycling of waste PET. DETAILED DESCRIPTION
[0021] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0022] The first aspect of the present invention provides a titanium-rare earth composite catalyst, wherein the titanium-rare earth composite catalyst comprises: a titanium-containing compound and a rare earth catalyst;
[0023] Wherein, the titanium-containing compound is selected from at least one of alkyl titanate, diol titanium, titanium phosphate, and organic-inorganic hybrid titanium;
[0024] Wherein, the rare earth catalyst is selected from acetylacetone rare earth catalyst.
[0025] In one embodiment of the present invention, preferably, the alkyl titanate is selected from at least one of tetraethyl titanate, tetrabutyl titanate, isopropyl titanate, tetraisobutyl titanate, titanium acetylacetonate, and di(acetylacetonato) diisopropyl titanate.
[0026] In one embodiment of the present invention, preferably, the titanium glycolate is titanium ethylene glycolate.
[0027] In one embodiment of the present invention, preferably, the organic-inorganic hybrid titanium is selected from any type of organic-inorganic hybrid titanium disclosed in the prior art, such as Venator's C-94 catalyst, PC catalyst, etc.
[0028] In one embodiment of the present invention, preferably, the titanium-containing compound is selected from at least one of titanium glycolate, tetrabutyl titanate, isopropyl titanate and titanium acetylacetonate.
[0029] In one embodiment of the present invention, preferably, the rare earth catalyst is selected from at least one of yttrium acetylacetonate, neodymium acetylacetonate, dysprosium acetylacetonate, terbium acetylacetonate and lanthanum acetylacetonate.
[0030] In one embodiment of the present invention, preferably, the mass ratio of the titanium-containing compound to the rare earth catalyst is 0.1:1-20:1; preferably 0.5:1-10:1.
[0031] In one embodiment of the present invention, preferably, the solubility of the titanium-containing compound in ethylene glycol (20°C) is <1g / 100g, preferably <0.5g / 100g, and more preferably <0.1g / 100g; the solubility of the rare earth catalyst in ethylene glycol (20°C) is <1g / 100g, preferably <0.5g / 100g. In the present invention, the titanium-rare earth composite catalyst is used for alcoholysis of polyethylene terephthalate. In order to make the catalyst easy to remove from the depolymerization system, the BHET catalyst residue is low. In addition to maintaining activity, the catalyst also needs to have as little solubility in diols as possible. A large number of experiments have shown that within the above solubility range, the residual amount of the catalyst in the final product BHET can be minimized.
[0032] A second aspect of the present invention provides a method for alcoholysis of polyethylene terephthalate, the method comprising:
[0033] (1) in the presence of a protective gas and a catalyst, subjecting an alcohol and a material containing polyethylene terephthalate to a depolymerization reaction to obtain a depolymerization liquid;
[0034] (2) purifying the depolymerization liquid to obtain a product containing bis(2-hydroxyethyl) terephthalate;
[0035] Wherein, the catalyst is the titanium-rare earth composite catalyst described in the first aspect of the present invention.
[0036] The polyethylene terephthalate-containing material can be waste PET bottle flakes, waste PET long fibers, waste PET short fibers, waste polyester foam materials, waste PET films or materials with a PET content of ≥75wt%.
[0037] In one embodiment of the present invention, preferably, in step (1), the alcohol is a diol, preferably at least one selected from ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, and 1,6-hexanediol.
[0038] In one embodiment of the present invention, preferably, in step (1), the protective gas is nitrogen.
[0039] In one embodiment of the present invention, preferably, in step (1), the mass ratio of the polyethylene terephthalate-containing material to the alcohol is 1:2-1:6, preferably 1:2.5-1:5. If the amount of alcohol added is too small, and is lower than the above range, the depolymerization reaction will be insufficient, the oligomers will increase, and the yield of the final product BHET will be affected.
[0040] In one embodiment of the present invention, preferably, in step (1), the titanium-rare earth composite catalyst is 0.05-0.5wt% of the polyethylene terephthalate material; preferably 0.08-0.2wt%. If the amount of the titanium-rare earth composite catalyst added is too large, exceeding the above range, the amount of the catalyst residue in the final product BHET will increase, affecting the regeneration of the catalyst.
[0041] In one embodiment of the present invention, preferably, in step (1), the reaction temperature of the depolymerization reaction is 190-250° C., preferably 200-230° C. If the reaction temperature is too low, the depolymerization reaction will be incomplete, the oligomers will increase, and the yield of the final product BHET will be affected.
[0042] In one embodiment of the present invention, preferably, in step (1), the reaction pressure of the depolymerization reaction is 0.2-0.6 MPa, preferably 0.35-0.5 MPa. If the reaction pressure is too low, the depolymerization reaction will be insufficient, the oligomers will increase, and the yield of the final product BHET will be affected.
[0043] In one embodiment of the present invention, preferably, in step (1), the reaction time of the depolymerization reaction is 1-5 hours, preferably 2-4 hours. If the reaction time is too short, the depolymerization reaction will be insufficient, the oligomers will increase, and the yield of the final product BHET will be affected.
[0044] In one embodiment of the present invention, preferably, in step (2), the purification process comprises:
[0045] (i) filtering the depolymerization solution to remove undepolymerized matter in the depolymerization solution;
[0046] (ii) mixing the obtained filtrate with water and separating them to obtain a clarified liquid;
[0047] (iii) cooling the clarified liquid for crystallization and filtering it to obtain a high-purity BHET product.
[0048] In one embodiment of the present invention, preferably, in step (i), the filtration is performed using a screening device with a pore size of 10-25 μm, such as a funnel with a pore size of 10-25 μm.
[0049] In one embodiment of the present invention, preferably, in step (ii), the mass ratio of the depolymerization liquid to water is 1:2-1:10; preferably 1:2-1:5.
[0050] In one embodiment of the present invention, preferably, the stirring and mixing temperature in step (ii) is 60-100°C, preferably 65-80°C.
[0051] In one embodiment of the present invention, preferably, the stirring and mixing time in step (ii) is 1-3 hours.
[0052] In one embodiment of the present invention, preferably, the cooling crystallization in step (iii) includes crystallization at 0-30°C for 2-24 hours. In a further preferred embodiment, the crystallization process is: first crystallize at 15-30°C for 5-20 hours, and then crystallize at 0-5°C for 0.5-5 hours.
[0053] The present invention will be described in detail below through examples.
[0054] In the following examples, the depolymerization rate of polyethylene terephthalate is shown in (Formula 1), and the yield of the product BHET is shown in (Formula 2), wherein the molecular weight of BHET is 254 g / mol and the molecular weight of the PET repeating unit is 192 g / mol.
[0055]
[0056]
[0057] Example 1
[0058] 3 g of titanium acetylacetonate and 3 g of yttrium acetylacetonate were stirred evenly in a sample bottle to prepare a titanium-rare earth composite catalyst A.
[0059] Waste PET bottle flakes (hereinafter referred to as PET) and ethylene glycol are added to a reactor in a mass ratio of 1:5, and 0.1wt% (based on the mass of PET) of titanium-rare earth composite catalyst A is added, and the air in the reactor is replaced with nitrogen. After confirming the air tightness of the reactor, a certain amount of nitrogen is introduced to make the pressure in the reactor reach 0.4MPa, and stirring is turned on. The temperature in the reactor is set to 200°C. After the temperature of the reactor rises to the set temperature, the timing is started, and the depolymerization reaction is carried out for 3 hours to obtain a depolymerization product. The PET depolymerization rate is 100%, the total content of products with a degree of polymerization of oligomers of 1-3 in the alcoholysis product is 99.3wt%, and BHET accounts for 94.3wt% in the depolymerization product.
[0060] The depolymerization product was filtered while hot at 120°C to obtain a filtrate, and deionized water was added at a ratio of filtrate: water = 1:2. After stirring in a water bath at 80°C for 2 hours, the filtrate was filtered to obtain a filtrate. The filtrate was crystallized at room temperature for 8 hours, and then cooled and crystallized at 0-5°C for 2 hours. Crystalline BHET was obtained by suction filtration, and dried in a drying oven at 70°C for 8 hours and weighed. The yield of the target product BHET was 77.8%, and the purity of BHET was 98.1wt%.
[0061] Based on this example, it can be seen that the titanium-rare earth composite catalyst of the present invention has high efficiency and high selectivity, and BHET has high yield and high purity.
[0062] Example 2
[0063] The method of Example 1 is followed, except that the composite catalyst is titanium ethylene glycol and neodymium acetylacetonate in a mass ratio of 1.6:1, the amount of the catalyst is 0.1wt% of the weight fraction of PET, PET and ethylene glycol are added to the reactor in a mass ratio of 1:4 for depolymerization reaction, and the reaction temperature is 210°C.
[0064] In Example 2, the PET depolymerization rate is 100%, the total amount of products with oligomer polymerization degree of 1-3 in the alcoholysis product is 99.2%, BHET accounts for 94.2% of the depolymerization product, the yield of depolymerized monomer BHET is 77.0%, and the purity of BHET is 98.0%.
[0065] Example 3
[0066] The method of Example 1 is followed, except that the composite catalyst is titanium glycolate and dysprosium acetylacetonate in a mass ratio of 4:1, PET and ethylene glycol are added to the reactor in a mass ratio of 1:4.5, and the amount of catalyst added is 0.08wt% of the mass fraction of PET.
[0067] In Example 3, the PET depolymerization rate is 100%, the total amount of products with oligomer polymerization degree of 1-3 in the alcoholysis product is 99.0%, BHET accounts for 93.6% of the depolymerization product, the yield of depolymerized monomer BHET is 76.9%, and the purity of BHET is 98.0%.
[0068] Example 4
[0069] The method of Example 3 is followed, except that the composite catalyst is isopropyl titanate and lanthanum acetylacetonate in a mass ratio of 3:1, the amount of the catalyst is 0.2 wt% of the weight fraction of PET, and the depolymerization temperature is 210°C.
[0070] In Example 4, the PET depolymerization rate was 100%, the total amount of oligomers with a degree of polymerization of 1-3 in the alcoholysis product was 99.4%, BHET accounted for 94.5% of the depolymerization product, the target monomer BHET yield was 79.6%, and the BHET purity was 98.0%.
[0071] Example 5
[0072] The method of Example 1 was followed, except that PET and ethylene glycol were added to the reactor at a mass ratio of 1:3, and the depolymerization pressure was 0.3 MPa.
[0073] In Example 5, the PET depolymerization rate was 100%, the total amount of oligomers with a degree of polymerization of 1-3 in the alcoholysis product was 98.2%, BHET accounted for 90.5% of the depolymerization product, the yield of depolymerized monomer BHET was 74.8%, and the purity of BHET was 97.8%.
[0074] Example 6
[0075] The method of Example 1 is followed, except that the composite catalyst is n-butyl titanate and terbium acetylacetonate in a mass ratio of 1:1, PET and ethylene glycol are added to the reactor in a mass ratio of 1:6, and the depolymerization reaction temperature is 190°C.
[0076] In Example 6, the PET depolymerization rate was 100%, the total amount of oligomers with a degree of polymerization of 1-3 in the alcoholysis product was 99.3%, BHET accounted for 94.5% of the depolymerization product, the yield of depolymerized monomer BHET was 79.9%, and the purity of BHET was 98.0%.
[0077] Example 7
[0078] The method of Example 3 was followed, except that the amount of catalyst used was 0.15 wt % and the depolymerization pressure was 0.5 MPa.
[0079] In Example 7, the PET depolymerization rate was 100%, the total amount of oligomers with a degree of polymerization of 1-3 in the alcoholysis product was 99.3%, BHET accounted for 94.0% of the depolymerization product, the yield of depolymerized monomer BHET was 78.9%, and the purity of BHET was 97.5%.
[0080] Example 8
[0081] The method of Example 3 was followed, except that the amount of catalyst added was 0.1 wt%, the reaction pressure was 0.35 MPa, and the reaction time was 4 hours.
[0082] In Example 8, the PET depolymerization rate was 100%, the total amount of oligomers with a degree of polymerization of 1-3 in the alcoholysis product was 99.1%, BHET accounted for 94.1% of the depolymerization product, the yield of depolymerized monomer BHET was 77.2%, and the purity of BHET was 97.9%.
[0083] Example 9
[0084] 83 g of homemade BHET monomer and 0.52 g of tetrabutyl titanate were added to a three-necked flask, and the temperature was gradually raised to 190°C under a nitrogen atmosphere. The reaction was carried out for 1 hour, and then the vacuum distillation device was replaced, the temperature was raised to 280°C, and the vacuum degree of the system was gradually adjusted to less than 300 Pa. After reacting for 2.5 hours, a PET product was obtained with a number average molecular mass of 23,000 g / mol.
[0085] Comparative Example 1
[0086] Waste PET bottle flakes and ethylene glycol are added to a reactor in a mass ratio of 1:4.5, and 0.3wt% (based on the mass of PET) of tetrabutyl titanate is added. The depolymerization pressure is 0.4MPa, the depolymerization temperature is 200°C, and the depolymerization time is 3 hours to obtain a depolymerization product. The PET depolymerization rate is 100%, the total amount of products with a degree of polymerization of oligomers of 1-3 in the alcoholysis products is 97.6%, BHET accounts for 90.7% of the depolymerization products, the yield of depolymerized monomer BHET is 60.8%, and the purity of BHET is 96.7%.
[0087] The experimental results of Examples 1-8 and Comparative Example 1 are summarized in Table 1.
[0088] Table 1
[0089]
[0090]
[0091] Table 1 (continued)
[0092]
[0093] From the results in Table 1, it can be seen that Examples 1-8 using the technical solution of the present invention have significantly better effects than Comparative Example 1 in terms of the total amount of products with a degree of polymerization of oligomers of 1-3, the yield and purity of the depolymerized monomer BHET, and Examples 1-4 and 6-8 have significantly better effects in terms of the proportion of BHET in the depolymerized products. In Example 5, the proportion of BHET in the depolymerized products is low due to the low reaction pressure, but it is better than Comparative Example 1 in terms of other technical effects listed in Table 1. While achieving the above-mentioned significantly better effects, Examples 1-8 significantly reduce the amount of titanium-rare earth composite catalyst used compared to Comparative Example 1. The results of Example 9 also prove that the BHET obtained by the method of the present invention can be directly used to prepare PET polyester products or other high value-added products, realizing the closed-loop recycling of PET.
[0094] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A titanium-rare earth composite catalyst, wherein: The titanium-rare earth composite catalyst comprises: a titanium-containing compound and a rare earth catalyst; Wherein, the titanium-containing compound is selected from at least one of alkyl titanate, diol titanium, titanium phosphate, and organic-inorganic hybrid titanium; Wherein, the rare earth catalyst is selected from acetylacetone rare earth catalyst.
2. The titanium-rare earth composite catalyst according to claim 1, wherein The alkyl titanate is selected from at least one of tetraethyl titanate, tetrabutyl titanate, isopropyl titanate, tetraisobutyl titanate, titanium acetylacetonate, and di(acetylacetonato) diisopropyl titanate; And / or, the titanium glycolate is titanium ethylene glycol; Preferably, the titanium-containing compound is selected from at least one of titanium glycolate, tetrabutyl titanate, isopropyl titanate and titanium acetylacetonate.
3. The titanium-rare earth composite catalyst according to claim 1 or 2, wherein The rare earth catalyst is selected from at least one of yttrium acetylacetonate, neodymium acetylacetonate, dysprosium acetylacetonate, terbium acetylacetonate and lanthanum acetylacetonate.
4. The titanium-rare earth composite catalyst according to any one of claims 1 to 3, wherein The mass ratio of the titanium-containing compound to the rare earth catalyst is 0.1:1-20:1, preferably 0.5:1-10:
1.
5. The titanium-rare earth composite catalyst according to any one of claims 1 to 4, wherein The solubility of the titanium-containing compound in ethylene glycol (20° C.) is less than 1 g / 100 g, preferably less than 0.5 g / 100 g, and more preferably less than 0.1 g / 100 g; Preferably, the solubility of the rare earth catalyst in ethylene glycol (20° C.) is <1 g / 100 g, preferably <0.5 g / 100 g.
6. A method for alcoholysis of polyethylene terephthalate, the method comprising: (1) in the presence of a protective gas and a catalyst, subjecting an alcohol and a material containing polyethylene terephthalate to a depolymerization reaction to obtain a depolymerization liquid; (2) purifying the depolymerization liquid to obtain a product containing bis(2-hydroxyethyl) terephthalate; Wherein, the catalyst is the titanium-rare earth composite catalyst as described in any one of claims 1-5.
7. The method according to claim 5, wherein: In step (1), the alcohol is a diol, preferably at least one selected from ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, and 1,6-hexanediol.
8. The method according to claim 5 or 6, wherein: In step (1), the mass ratio of the polyethylene terephthalate to the alcohol is 1:2-1:6; preferably 1:2.5-1:
5.
9. The method according to any one of claims 5 to 7, wherein: In step (1), the catalyst is 0.05-0.5wt% of polyethylene terephthalate; preferably 0.08-0.2wt%.
10. The method according to any one of claims 5 to 8, wherein: In step (1), the reaction temperature of the depolymerization reaction is 190-250°C; preferably 200-230°C.
11. The method according to any one of claims 5 to 9, wherein: In step (1), the reaction pressure of the depolymerization reaction is 0.2-0.6 MPa, preferably 0.35-0.5 MPa.
12. The method according to any one of claims 5 to 10, wherein: In step (1), the reaction time of the depolymerization reaction is 1-5 h, preferably 2-4 h.
Citation Information
Patent Citations
Manufacture of esters
CN101146761A
Method for depolymerizing polyethylene terephthalate with ethylene glycol
CN104447341A
Method for depolymerising oxygenated polymer materials by nucleophilic catalysis
CN112673058A
Catalyst system and application in use for synthesizing degradable polyester
CN1796434A
Metal acetylacetonates as transesterification catalysts
US20060052572A1
Cited By
Recycling method of solar back plate
CN120248420A
Method for generating BHET based on DBU-SiO2 catalyst depolymerization
CN121949105A
Bis (2-hydroxyethyl) terephthalate and polybutylene terephthalate as well as preparation method and application of bis (2-hydroxyethyl) terephthalate and polybutylene terephthalate
CN122102895A
Fat aromatic copolyester as well as preparation method and application thereof
CN122103533A